Multiplexed readout of MMC detector arrays using non-hysteretic rf-SQUIDs - Kempf, Sebastian; Wegner, Mathias; Gastaldo, Loredana; Fleischmann, Andreas; Enss, Christian (Journal of low temperature physics, 2014)
Metallic magnetic calorimeters (MMCs) are widely used for various experiments in fields ranging from atomic and nuclear physics to X-ray spectroscopy, laboratory astrophysics or material science. Whereas in previous experiments single pixel detectors or small arrays have been used, for future applications large arrays are needed. Therefore, suitable multiplexing techniques for MMC arrays are currently under development. A promising approach for the readout of large arrays is the microwave SQUID multiplexer that employs non-hysteretic rf-SQUIDs to create a frequency shift of high $$Q$$Qresonators that is in accordance with the detector signal and that can be monitored by using standard microwave measurement techniques. In this paper we discuss the design of a recently developed and fabricated 64 pixel detector array with integrated microwave SQUID multiplexer that was produced to test the suitability of this readout technique. The characterization of dc-SQUIDs with virtually identical washer design compared to the rf-SQUIDs of the SQUID multiplexer revealed that the crucial SQUID parameters such as the critical current of the Josephson junctions or the washer inductance are close to the design values and anticipates a successful operation of the SQUID multiplexer.
Published online: 31 December 2013
Gesehen am 28.07.2020